Keutamaan Ibu dalam Hak Asuh Anak Perspektif Pendidikan: Analisis Hadits Tarbawi - Ilyasa, Faisal Fauzan; Rahardja, Muhammad Nurfaizi Arya; Masrukhin, Akhmad Rudi; Zulaiha, Mailinda Anis; Sumarna, Elan (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
This study aims to analyze the mother's role in child custody after divorce from the perspective of tarbawi hadith, focusing on integrating Islamic educational values. A qualitative approach with descriptive-analytical methods and taḥlīlī analysis techniques was employed. Data were collected through library research utilizing primary and secondary sources from classical and contemporary Islamic literature. The research procedure included theme selection, hadith selection, takhrij analysis, and interpretation of educational values. The findings highlight that tarbawi hadith legitimizes maternal priority in custody as long as moral and spiritual criteria are met, with profound educational implications. Mothers, as the first educators, play a strategic role in ensuring emotional stability, supporting psychological development, and internalizing children's spiritual values. These findings significantly contribute to the Islamic educational perspective on child-rearing, particularly post-divorce.